2017
DOI: 10.3390/nu9030230
|View full text |Cite
|
Sign up to set email alerts
|

Fructose and NAFLD: The Multifaceted Aspects of  Fructose Metabolism

Abstract: Among various factors, such as an unhealthy diet or a sedentarity lifestyle, excessive fructose consumption is known to favor nonalcoholic fatty liver disease (NAFLD), as fructose is both a substrate and an inducer of hepatic de novo lipogenesis. The present review presents some well-established mechanisms and new clues to better understand the pathophysiology of fructose-induced NAFLD. Beyond its lipogenic effect, fructose intake is also at the onset of hepatic inflammation and cellular stress, such as oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
205
1
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(228 citation statements)
references
References 97 publications
(128 reference statements)
12
205
1
10
Order By: Relevance
“…Also fructose phosphorylation leads to depletion of ATP, which stimulates increased uric acid synthesis which in turn stimulates production of ROS [81]. Lastly fructose can induce mitochondrial disturbance which lead to disequilibrium between De novo Lipogenesis and VLDL, which promotes alteration of respiratory chain and uncoupling of oxidative phosphorylation with excess ROS production [82,83].…”
Section: Dietary Factorsmentioning
confidence: 99%
“…Also fructose phosphorylation leads to depletion of ATP, which stimulates increased uric acid synthesis which in turn stimulates production of ROS [81]. Lastly fructose can induce mitochondrial disturbance which lead to disequilibrium between De novo Lipogenesis and VLDL, which promotes alteration of respiratory chain and uncoupling of oxidative phosphorylation with excess ROS production [82,83].…”
Section: Dietary Factorsmentioning
confidence: 99%
“…Simple carbohydrates, such as glucose and fructose generate abundant levels of glycerol-3-phosphate, which can be used in triglyceride synthesis. Moreover, as fructokinase is not regulated by insulin, excessive fructose can lead to unregulated production of acetyl-Co-A, which is in turn converted to triglycerides (Jegatheesan & De Bandt, 2017). Diets deficient in essential nutrients can also result in fatty liver.…”
Section: Animal Models Of Nafldmentioning
confidence: 99%
“…because this promotes ectopic triglyceride synthesis and, thereby, increases the risk of developing nonalcoholic fatty liver disease (NAFLD). However, it has been observed that ingestion of nondigestible carbohydrates, including oligosaccharides classified as FODMAPs, may also protect against the onset of NAFLD (4,22).…”
Section: Is a Low-fodmap Diet Recommendable To All?mentioning
confidence: 99%